Literary text in high school: some elements of reflection on its learning objectives - BOUACHE, Nasredine (Journal of Human Sciences, 2020)
The question of the objectives assigned to literary texts is today to be taken seriously. This is the idea we wanted to discuss from the examination of three textbooks for secondary school classes. As a result, the strengthening of fundamentals (reading, writing) and cultural enhancement are some of the objectives associated with this object of study. The learner must first learn to read better but also to write better for a better mastery of the language. The cultural enhancement of the student is also included in textbooks as a goal. All this enlighten us, therefore, on this leap of realism which indicates the direction of the walk in which the Algerian school is engaged today.